Korelasi Antara Kemampuan Tahfidzul Qur’an Dengan Prestasi Belajar Siswa Pada Bidang Studi Al-Qur’an Hadits Di Ma Unggulan Darul ‘Ulum STEP-2 IDB Rejoso Peterongan Jombang - Siti Erliana Almatin; Muhammad Heri Prianto; Muhammad Ainun Ikhwan Rusyada (Jurnal Pendidikan Agama Islam Miazhar, 2023)
This study explains the correlation between the ability to memorize the Qur'an and student achievement in the field of Al-Qur'an Hadith at MA Unggulan Darul 'Ulum STEP-2 IDB Rejoso Peterongan Jombang. The aims of this study were 1) to find out the implementation of the tahfidzul Qur'an program for class XI tahfidz Al-Qur'an students at Madrasah Aliyah Unggulan Darul Ulum STEP-2 IDB Rejoso Peterongan Jombang 2) to find out how students' learning achievements of Al-Qur'an Hadith class XI tahfidz Al-Qur'an at Madrasah Aliyah Unggulan Darul Ulum STEP-2 IDB Rejoso Peterongan Jombang 3) To find out the correlation between the ability of tahfidz Al-Qur'an and student achievement of class XI tahfidz Al-Qur'an in Al-Qur'an study field -Qur'an Hadith at Madrasah Aliyah Featured Darul Ulum STEP-2 IDB Rejoso Peterongan Jombang. This type of research is quantitative with a bivariate correlation design that uses product moment correlation statistics. This research uses non-probability sampling technique with saturation method. Using observational data collection techniques and documentation. The sample in this study were all students of class XI tahfidz Al-Qur'an at MA Unggulan Darul Ulum STEP-2 IDB Rejoso Peterongan Jombang. The results showed that an average of 316 was obtained from the tahfidz Al-Qur'an report cards for class XI tahfidz Al-Qur'an students. Then an average of 262 is obtained from the learning achievement of class XI tahfidz Al-Qur'an students. Then supported by product moment correlation results, the value of r count = 0.859 and r table = 0.444 is obtained. It can be concluded that r count > r table, then Ho is rejected, H1 is accepted. Based on the results of this study it can be stated that the ability between students' tahfidz Al-Qur'an and student achievement in class XI tahfidz Al-Qur'an in the field of study of Al-Qur'an Hadith at MA Unggulan Darul Ulum STEP-2 IDB Rejoso Peterongan Jombang is very Good